Biochemical properties of fodder additives based on fermented poultry wastes and their effects on broiler productivity - V.G. Volik; D.Yu. Ismailova; V.S. Lukashenko; I.P. Saleeva; T.V. Fedorova; E.A. Ovseychik; E.V. Zhuravchuk; S.V. Zinovyev (Учёные записки Казанского университета: Серия Естественные науки)
The wastes of broiler slaughter and carcass processing – poultry by-products (feathers, blood, bones, meat trimmings, etc.) – are the substantial part of the initial live bodyweight of slaughtered broilers (up to 30%); these by-products, with hydrolysates being especially promising, can serve as a source of animal protein in diets for poultry. In this study, we determined the biochemical properties of the fermented protein additives produced by short-term thermal treatment and subsequent enzymatic hydrolysis of collagen- and keratin-containing poultry wastes. The dry protein additive based on the keratin-containing wastes featured average moisture content 4.57%, crude protein content 86.52%, crude fat content 2.25%, ash content 2.04%; the respective parameters in the dry additive based on the collagen-containing wastes after high-temperature treatment and enzymatic hydrolysis were 2.57, 45.4, 23.29, and 24.04%. The digestibility of the dry keratin- and collagen-based additives after the two-stage productive cycle was 92.0 and 85.0%, respectively. Certain biochemical parameters of these two additives were determined (antioxidative capacity, molecular weight distribution of peptides, profile of volatiles). The analysis of volatiles profile in the keratin-based additive showed that it contained 37 main ingredients, including aliphatic acids and their amides, indole and its derivatives, alcohols, amides of aromatic acids and their derivatives, sulphur-containing substances. The latter are probably responsible for the characteristic odor of the keratin-based product. It was found that the fermented keratin- and collagen-based additives contain primarily peptides with low (< 5 KDa) and medium (10–25 KDa) molecular weights. The antioxidative capacity of the additives in relation to peroxide radical varied in the range of 250–300 μmoles of trolox equivalent per 1 g; over 99.9% of this capacity was presented by hydrophilic antioxidants. Trials on broilers with the substitution of the fermented additives for fish meal in the diets proved that the additives do not compromise the growth efficiency and productive performance.